Performance of Using Spark Plugs and Fuels Variations on 4-Stroke Motorcycle Engines - Al. Aziz.R, M. Shafwallah; Arifin, Agus Choirul; Wahyudi, Noorsakti; Bisono, Rahayu Mekar; Dharmawangsa, Rendy Vito (International Journal of Science, Engineering, and Information Technology, 2023)
In the motorcycle ignition system, spark plugs play an important role in sparking the sparks needed to burn fuel with compressed air. The purpose of this research is to determine the ratio of torque, power, fuel consumption in 4-stroke gasoline engines produced from standard, two legged, platinum, and iridium spark plugs using pertalite, pertamax and pertamax turbo fuel. This test uses a 4 stroke 150 CC gasoline motorcycle. Motorcycle engine performance testing is done using a dynotest. The results obtained were the peak power in the Pertamax fuel test using iridium spark plugs of 14.3 Hp at 8000 RPM engine speed, 0.71% higher than Pertamax fuel using standard manufacturer spark plugs. Then the highest torque from all test data is on the Pertamax fuel test using iridium spark plugs of 13.43 Nm running the 7000 RPM engine which is 0.22% higher than Pertamax fuel using standard manufacturer spark plugs. Meanwhile, the lowest or most efficient fuel consumption was in testing the Pertamax turbo fuel using an iridium spark plug of 0.059 kg/kWh running a 6000 RPM engine, 1.69% more efficient compared to Pertamax turbo fuel using a standard manufacturer's spark plug.